Ultrasound-Estimated Index Versus Measured Volume of Amniotic Fluid at Caesarean Delivery: Accuracy and Perinatal Outcomes: Accuracy of Ultrasound in Estimating Amniotic Fluid at Delivery - Sohail, Shaherzad; Iqbal, Faiza; Imran, Sanya; Mushtaq, Rabia; Altaf, Omar (Journal of University College of Medicine and Dentistry, 2025)
Objective: To assess the reliability of ultrasound-based amniotic fluid index (AFI) in estimating amniotic fluid volume by comparing it with intraoperative findings during caesarean section, and to evaluate its association with neonatal clinical outcomes in low-risk term pregnancies. Methodology: This prospective observational study was conducted at the Department of Obstetrics and Gynaecology, Shalamar Hospital, Lahore, from January to June 2024. A total of 100 pregnant women between 37 and 40 weeks of gestation who underwent caesarean section, were enrolled. Participants were divided into two groups based on AFI measured by ultrasound: Group 1 with low AFI (<5 cm) and Group 2 with normal AFI (5–25 cm). Intraoperative amniotic fluid volume was estimated using a suction apparatus. Neonatal outcomes, including Apgar scores at 1 and 5 minutes and NICU admissions, were recorded and compared. Results: In the low AFI group, 74% of patients had low amniotic fluid volume confirmed during surgery, while 26% had normal levels. In the normal AFI group, 80% had normal intraoperative fluid volume, and 20% showed reduced levels. Poor Apgar scores at 1 minute were seen in 62% of neonates in the low AFI group versus 16% in the normal group. At 5 minutes, 12% in the low AFI group and 2% in the normal group had low scores. NICU admission was required in 34% of neonates in the low AFI group compared to 8% in the normal group (p < 0.05). Conclusion: There is a moderate correlation between AFI and intraoperative fluid volume. Low AFI is associated with adverse neonatal outcomes, supporting its role in antenatal risk assessment.